Lunar and mars gravity induce similar changes in spinal motor control as microgravity - Swanenburg, Jaap; Easthope, Christopher A.; Meinke, Anita; Langenfeld, Anke; Green, David A.; Schweinhardt, Petra (Frontiers in Physiology, 2023)
Humans sresend to the Moon or possibly even to Mars. It is therefore, important to know potential physiological effects of a prolonged stay in space and to minimize possible health risks to astronauts. Spinal motor control strategies seems change during microgravity induced by parabolic flight. The way in which spinal motor control strategies change during partial microgravity, such as that encountered on the Moon and on Mars, is not known. Spinal motor control measurements were performed during Earth, lunar, Mars, and micro-gravity conditions and two hypergravity conditions of a parabola. Three proxy measures of spinal motor control were recorded: spinal stiffness of lumbar L3 vertebra using the impulse response, muscle activity of lumbar flexors and extensors using surface electromyography, and lumbar curvature using two curvature distance sensors placed at the upper and lower lumbar spine. The participants were six females and six males, with a mean age of 33 years (standard deviation: 7 years). Gravity condition had a statistically significant (Friedmann tests) effect spinal stiffness (p < 0.001); on EMG measures (multifidus (p = 0.047), transversus abdominis (p < 0.001), and psoas (p < 0.001) muscles) and on upper lumbar curvature sensor (p < 0.001). No effect was found on the erector spinae muscle (p = 0.063) or lower curvature sensor (p = 0.170). Post hoc tests revealed a significant increase in stiffness under micro-, lunar -, and Martian gravity conditions (all p's < 0.034). Spinal stiffness decreased under both hypergravity conditions (all p's ≤ 0.012) and decreased during the second compared to the first hypergravity condition (p = 0.012). Micro-, lunar-, and Martian gravity conditions resulted in similar increases in spinal stiffness, a decrease in transversus abdominis muscle activity, with no change in psoas muscle activity and thus modulation of spinal motor stabilization strategy compared to those observed under Earth’s gravity. These findings suggest that the spine is highly sensitive to gravity transitions but that Lunar and Martian gravity are below that required for normal modulation of spinal motor stabilization strategy and thus may be associated with LBP and/or IVD risk without the definition of countermeasures.